The Influence of Underpricing to IPO Aftermarket Performance: Comparison between Fixed Price and Book Building System on the Indonesia Stock Exchange - Utamaningsih, Arni (International Journal of Economics and Financial Issues, 2017)
This study discusses the IPO stock trading in Indonesia Stock Exchange in asymmetry information conditions between heterogen investors. Underpricing is a central issue in the IPO trading, where the price conditions were considered too low to below the market price. This condition is very detrimental to the company's prime, but also a signal that the company has a good reputation. IPO with strong conditions indicated has well performance in the aftermarket period. This condition is referred to as the contradictions and an anomali in Financial Management. This study aimed to assess the effect of underpricing on the stock performance in the aftermarket period. Indonesia Stock Exchange in its history ever implement the fixed price and bookbuilding IPO trading systems. This study intends to compare the IPO aftermarket performance between the bookbuilding and fixed price period. This study intends to provide answers the question that the bookbuilding can reduce the uncertainty of new stock trading and to reduce the impact of asymmetry information in the aftermarket period. Keywords: Underpricing, Fixed Price System, Bookbuilding System, Aftermarket Period. JEL Classifications: E44, G1